Lipschitz-inspired HALRECT algorithm for derivative-free global optimization - Stripinis, Linas; Paulavičius, Remigijus (Journal of global optimization, 2024)
This article considers a box-constrained global optimization problem for Lipschitz-continuous functions with an unknown Lipschitz constant. Motivated by the famous DIRECT (DIviding RECTangles), a new HALRECT (HALving RECTangles) algorithm is introduced. A new deterministic approach combines halving (bisection) with a new multi-point sampling scheme in contrast to trisection and midpoint sampling used in most existing DIRECT-type algorithms. A new partitioning and sampling scheme uses more comprehensive information on the objective function. Four different strategies for selecting potentially optimal hyper-rectangles are introduced to exploit the objective function’s information effectively. The original algorithm HALRECT and other introduced HALRECT variations (twelve in total) are tested and compared with the other twelve recently introduced DIRECT-type algorithms on 96 box-constrained benchmark functions from DIRECTGOLib v1.1, and 96 perturbed their versions. Extensive experimental results are advantageous compared to state-of-the-art DIRECT-type global optimization. New HALRECT approaches offer high robustness across problems of different degrees of complexity, varying from simple—uni-modal and low dimensional to complex—multi-modal and higher dimensionality.